Stepping stones or shelter areas? The role of rock glaciers in context of Alpine deglaciation - Brighenti, Stefano; Bruno, M. C.; Tolotti, M.; Bertoldi, W. (Società Italiana di Ecologia, 2018)
Deglaciation is causing significant consequences on the hydrology of the Alpine watersheds and their lowland areas, which will be characterized by an increasing variability and hydrological stochasticity due to the loss of glaciers and the reduction of snow cover. On the other hand, given the greater climatic resilience of permafrost, this component of the cryosphere will play an increasingly important role in the hydroecology of high altitude basins. Rock glaciers are the most evident form of alpine permafrost and are the source of streams whose baseflow derives from the melting of interstitial ice. While streams fed by glacial melt (kryal), snow-melt and precipitation (rhithral) and groundwater (krenal) have been extensively investigated, little is known about the ecology of rock-glacier fed streams, despite their peculiar hydromorphological, physical and chemical characteristics . We investigated a high altitude Alpine basin in the South Tyrolean Alps (Solda Valley, Ortles -Cevadale Massif) to illustrate the ecological peculiarities of the streams fed by rock glacier in comparison with high altitude streams of different origins: glacial, spring and mixed. We sampled streams of different origin but with comparable geology and altitude within two sub-basins, for a total of 13 stations sampled in the three key moments of the summer season: peak of snow melting, ablation and recession. Preliminary community analysis of invertebrates, albeit with low taxonomic detail (genus / family), shows how the rock glacier streams, which share the same altitude of glacial-fed streams, are similar in composition, abundance and diversity to the streams of the valley floor. Therefore, a fundamental question arises, inherent the biogeographic role of rock glaciers in the context of deglaciation: are rockglacier fed streams stepping stones used by invertebrates to colonize high altitude areas, or rather hotspots of diversity in which cold-stenotherm taxa will they shelter after glaciers will melt and disappear?